2020
DOI: 10.1186/s12931-020-01396-y
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette-induced pulmonary inflammation and dysregulated repair are mediated by nAChR α7 receptor: role of nAChR α7 in SARS-CoV-2 Covid-19 ACE2 receptor regulation

Abstract: Electronic cigarette (e-cig) vaping is increasing rapidly in the United States, as e-cigs are considered less harmful than combustible cigarettes. However, limited research has been conducted to understand the possible mechanisms that mediate toxicity and pulmonary health effects of e-cigs. We hypothesized that sub-chronic e-cig exposure induces inflammatory response and dysregulated repair/extracellular matrix (ECM) remodeling, which occur through the α7 nicotinic acetylcholine receptor (nAChRα7). Adult wild-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 58 publications
8
85
1
3
Order By: Relevance
“…However, e-cig use in any case did not increase ACE2 expression, which has not been reported in the literature. One recent study exposing mice to nicotine-containing e-cig for 1 month has found induction of ACE2 after exposure to nicotine-containing e-cig [51]. In our dataset, humans were also exposed to nicotine-containing e-cig for at least 1 month, suggesting that the in vivo results may not replicate physiological exposure.…”
Section: Discussionmentioning
confidence: 75%
“…However, e-cig use in any case did not increase ACE2 expression, which has not been reported in the literature. One recent study exposing mice to nicotine-containing e-cig for 1 month has found induction of ACE2 after exposure to nicotine-containing e-cig [51]. In our dataset, humans were also exposed to nicotine-containing e-cig for at least 1 month, suggesting that the in vivo results may not replicate physiological exposure.…”
Section: Discussionmentioning
confidence: 75%
“…NAC may also block COVID-19 binding by disrupting disulfide bind within its receptor-binding domain [ 29 ]. In addition to epithelial, endothelial, and myocardial cells [ 30 , 31 ], ACE2 is expressed on T lymphocytes [ 32 ], macrophages [ 33 ], and hepatocytes [ [34] , [35] , [36] , [37] ]. ACE2 controls the expression of pro-inflammatory transcription factor Stat3 [ [38] , [39] , [40] , [41] , [42] , [43] ], which also modulates the production of reactive oxygen intermediates by complex I of the mitochondrial electron transport chain (ETC) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, e-cig use in any case did not increase ACE2 or TMPRSS2 expression, which has not been reported in the literature. One recent study exposing mice to nicotine-containing e-cigs for 1 month has found induction of ACE2 after exposure to nicotine-containing e-cigs [ 53 ]. In our dataset, humans were also exposed to nicotine-containing e-cigs for at least 1 month, suggesting that the in vivo results may not replicate physiological exposure.…”
Section: Discussionmentioning
confidence: 99%